Pelatihan Membuat Hand Sanitizer dan Obat Kumur Herbal kepada Siswa SMK Farmasi Saraswati 3 Denpasar - I Gede Made Suradnyana Suradnyana; Ni Made Dharma Shantini Suena; Debby Juliadi (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The prolonged Covid-19 pandemic has caused a decrease in income and an increase in expenditure to maintain body immunity and implement health protocols. One of the affected community groups is students of SMK Farmasi Saraswati 3 Denpasar, so many students are in arrears of school fees. Efforts need to reduce family expenses, especially for health protocols and body immunity. One of the efforts is to provide training in making handsanitizer and mouthwash from herbs. The training aims to enable students to make handsanitizer and mouthwash as well as health drinks that can be used by themselves and their families. Thus students can reduce the burden on the family, especially spending on implementing health protocols. The training lasted for two days, taking place at SMK Farmasi Saraswati 3 Denpasar and was attended by 22 participants. The training was carried out in two stages, explanations and discussions regarding handsanitizers and mouthwashes which were held on May 24 2022, followed by practice on making preparations on May 28 2022. Before and after the training, tests were carried out to determine the participants' level of knowledge regarding handsanitizers and mouthwashes. The test results showed an increase in the average knowledge score from 68.9 to 97.3. It can be concluded that the provision of training is able to increase the knowledge of participants. Further training is needed regarding the business aspects of the product so as to increase family income.